Curriculum Transformation in Islamic Higher Education for the Development of Public Administration Based on Islamic Principles - Dodi Abdulrohim; Budiharjo; Pandji Sukmana; T Herry Rachmatsyah; Gunawan Ari Nursanto (ISEDU : Islamic Education Journal, 2025)
This article explores the integration of Islamic values into public administration studies in Indonesia, highlighting the role of Islamic principles in shaping ethical and effective governance. With over 260 million people and a rich Islamic heritage, Indonesia presents a unique context for the development of public administration that harmonizes both religious and secular principles. The article reviews theoretical foundations, such as the concepts of Amanah (trust), Adil (justice), and Maslahah (public welfare), that are central to Islamic governance. It also examines how Islamic higher education institutions in Indonesia, particularly through the transformation from Islamic Institutes (IAIN) to State Islamic Universities (UIN), are integrating public administration into their curricula. The shift in educational structures aligns with national policy initiatives like Merdeka Belajar (Independent Learning), enabling students to gain practical governance experience. Despite progress, challenges such as outdated curricula and insufficient faculty training remain. The article discusses these challenges while emphasizing the potential for Islamic values to inform public administration, offering a model for other Muslim-majority countries in balancing religious principles with modern governance.